SYNCHRONOUS COMMUNICATION BETWEEN HIGHER EDUCATION INSTITUTIONS AND EMPLOYERS IN THE FIELD OF SOCIAL WORK - Beata Krahulcová; Olga Zelinkova (European Scientific Journal, ESJ, 2015)
Typical of post-communist and post-industrial development of society in Central Europe is inter alia the inability of a significant part of the population to keep pace with the global societal requirements. The statistical data of social security offices indicate that the disintegrated persons or persons at risk of disintegration represent about one third of the population. The complexity of the phenomenon and the size of social demand for professions dealing with it trigger the process of training for professional qualification of social workers and the competition between quantitative and qualitative requirements for vocational training and its standardisation. From the perspective of both the educators and employers, it is necessary to assess the importance of theoretical training and experiential learning of future social workers and also the employability of young graduates from social work study programmes in the labour market.